2017
DOI: 10.2147/oarrr.s131046
|View full text |Cite
|
Sign up to set email alerts
|

Repository corticotropin injection as adjunctive therapy in patients with rheumatoid arthritis who have failed previous therapies with at least three different modes of action

Abstract: ObjectiveMany types of treatment are available for patients with rheumatoid arthritis (RA), however, some patients fail to achieve remission. This report aims to determine the safety and efficacy of using repository corticotropin injection (RCI) as an adjunctive therapy in patients with RA refractory to at least three therapeutics with different mechanisms of action.MethodIn this open-label, interventional, single-group study, patients received 80 U RCI twice weekly via subcutaneous injection over 12 weeks. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The evidence for the clinical effectiveness of RCI in patients with RA was suggested in small open-label studies [19][20][21]. The current study was undertaken to confirm these findings in a larger population via a randomized, doubleblind, placebo-controlled withdrawal trial with an open-label run-in period.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The evidence for the clinical effectiveness of RCI in patients with RA was suggested in small open-label studies [19][20][21]. The current study was undertaken to confirm these findings in a larger population via a randomized, doubleblind, placebo-controlled withdrawal trial with an open-label run-in period.…”
Section: Introductionmentioning
confidence: 74%
“…1. All enrolled subjects received open-label RCI (1 ml, 80 U) subcutaneously twice weekly for 12 weeks (part 1), a dosage that previous studies suggest is effective [20,21]. Subjects were then assessed for treatment response using the DAS28-ESR, with thresholds of 2.6, 3.2, and 5.1 suggesting remission, LDA, and high disease activity, respectively [22,23].…”
Section: Methodsmentioning
confidence: 99%
“…Our study reinforces the effectiveness of RCI treatment in patients with active RA. 20 Of the nine patients treated with RCI, five responded to 40 U daily for 1 week and did not need a dose increase (patients 2, 3, 6, 8, and 9). One patient in the 80 U group had clinically significant improvement (patient 5).…”
Section: Discussionmentioning
confidence: 97%
“…Two patients have disease remission and three patients show low disease activity (117). Similarly, Gillis et al demonstrated that, after subcutaneous injection with RCI over 12 weeks, all six patients with refractory rheumatoid arthritis achieve significantly lower Disease Activity Score, decreased tender and swollen joint counts, and reduced physician global visual analog scale (118). In addition, significant improvement were also observed in terms of Health Assessment Questionnaire score (3/6), erythrocyte sedimentation rate (4/6), and C-reactive protein levels (4/6) (118).…”
Section: Acth and Inflammationmentioning
confidence: 88%